Death by smoothie - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery, 2022)
Freelance writer Jaine Austen and her cat Prozac investigate the murder of a demanding actress set to star in a play based on a short-lived zombie sitcom.